Effects of transformational leadership on empowerment and team effectiveness - (:unkn) unknown (My University, 2003)
The purpose of this article is to investigate transformational leadership in relation to empowerment and team effectiveness. As part of an integrative model of leadership, transformational leadership style of superiors is proposed to be related to the strength of subordinate empowerment and team effectiveness. A total of 152 employees from various industries rated their superiors’ transformational leadership behaviors and also how much they felt empowered. They also evaluated their teams’ effectiveness in terms of innovativeness, communication and team performance. Findings suggest that transformational leadership contributes to the prediction of subordinates’ self-reported empowerment and that the more a team's members experience team empowerment, the more effective the team will be. © 2003, MCB UP Limited
Keywords: Empowerment; Transformational leadership